2012
DOI: 10.1093/bja/aer499
|View full text |Cite
|
Sign up to set email alerts
|

Clinical validation of a continuous non-invasive haemodynamic monitor (CNAP™ 500) during general anaesthesia

Abstract: The new CNAP monitor showed an agreement with the IAP that is promising but did not match our predefined criteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 14 publications
2
42
0
Order By: Relevance
“…Their study results showed that the standard deviation of the difference between the two devices was approximately ± 12 mmHg at the mode (75 mmHg MAP). 95 While these authors did not calculate the limits of agreement, a rough estimate that does not take into account repeated measures suggests that the confidence intervals of standard NIBP are worse than those reported in a number of volume-clamp studies [e.g., Martina (Nexfin), 96 Weiss (Nexfin), 97 Jeleazcov (CNAP), 98 Jagadeesh (CNAP), 99 Dewhirst (CNAP), 100 Tobias (CNAP), 101 and Ilies (CNAP)] 102 but similar to those in other volume-clamp studies [Biais (CNAP), 103 Hahn (CNAP), 104 McCarthy 2012 (CNAP), 105 and Schramm (CNAP)]. 106 At the extremes (significantly above or below a MAP of 75 mmHg), when accurate measurement of blood pressure is increasingly important, NIBP performance deteriorated.…”
Section: Clinical Contextsupporting
confidence: 68%
“…Their study results showed that the standard deviation of the difference between the two devices was approximately ± 12 mmHg at the mode (75 mmHg MAP). 95 While these authors did not calculate the limits of agreement, a rough estimate that does not take into account repeated measures suggests that the confidence intervals of standard NIBP are worse than those reported in a number of volume-clamp studies [e.g., Martina (Nexfin), 96 Weiss (Nexfin), 97 Jeleazcov (CNAP), 98 Jagadeesh (CNAP), 99 Dewhirst (CNAP), 100 Tobias (CNAP), 101 and Ilies (CNAP)] 102 but similar to those in other volume-clamp studies [Biais (CNAP), 103 Hahn (CNAP), 104 McCarthy 2012 (CNAP), 105 and Schramm (CNAP)]. 106 At the extremes (significantly above or below a MAP of 75 mmHg), when accurate measurement of blood pressure is increasingly important, NIBP performance deteriorated.…”
Section: Clinical Contextsupporting
confidence: 68%
“…In critically ill patients, continuous monitoring of hemodynamic parameters (especially monitoring of basic vital parameters like heart rate and blood pressure [BP]) is required. Different methods for continuous noninvasive BP monitoring have been described [1][2][3][4][5][6][7][8][9]. Among others, there are BP monitoring systems providing a continuous BP waveform based on photoplethysmography [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Different methods for continuous noninvasive BP monitoring have been described [1][2][3][4][5][6][7][8][9]. Among others, there are BP monitoring systems providing a continuous BP waveform based on photoplethysmography [1][2][3][4][5]. In addition, the applanation tonometry method with a sensor placed over the radial artery has been demonstrated to be able to provide a BP waveform and BP values in a noninvasive and continuous manner [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The non‐acceptable accuracy of the Task Force Monitor in estimating SBP is not in accordance with other studies (Hahn et al ., ; Ilies et al ., ). We acknowledge that our adjustment of adding 16 mmHg and subtracting 4 mmHg from the Task Force Monitor's measurements of SBP and DBP, respectively, might have distorted the estimations.…”
Section: Discussionmentioning
confidence: 99%